Faktor - Faktor yang Memengaruhi Profitabilitas pada Perusahaan Subsektor Investment Company di BEI Periode 2015 – 2019 - Reny Aziatul Pebriani; Rafika Sari (Universitas Indo Global Mandiri)
The aim of this study is to determine and analyse the effect of ESOP, leverage, and the size of the company partially and simultaneously to the profitability of the Investment Company Subsector Company in IDX Period 2015-2019. The data used in this study is library studies and documentation. Sample selection in this study using nonprobability purposive sampling technique. The data analysis method used is multiple linear regression analysis. The results prove that ESOP and company size partially have no significant effect on profitabilitas, but leverage has a significant effect on profitability. Then simultaneously ESOP, Leverage, and Company Size have no effect on profitability. The results of research with Agency theory and signal theory, ESOP is expected to increase the loyalty of the company manager to the owner of the company in improving profitability, and ESOP does not affect the contribution of profitability information of a company in assessing the condition of a company, between the relationship of the manager and the owner of the company. Leverage, in the explanation of signal theory is one of the factors that influence in providing information to investors on the profitability of acompany. Size of the company is determined by the management steps to manage the company's profit as best as possible, which we know companies with large scale does not necessarily have a good company performance also in improving its profitability. This research is expected to help companies to improve the profitability of thecompany.Keywords: ESOP, leverage, company size, profitabilitas